2015
DOI: 10.12965/jer.150196
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 8 weeks of pre-season training on body composition, physical fitness, anaerobic capacity, and isokinetic muscle strength in male and female collegiate taekwondo athletes

Abstract: The purpose of the study was to determine the effect of 8 weeks pre-season training on body composition, physical fitness, anaerobic capacity, and isokinetic strength in collegiate taekwondo athletes. Thirty-four collegiate athletes (male: 22, female: 12) participated. Body composition, bone mineral density, physical fitness, anaerobic capacity, and isokinetic muscle strength were tested. After statistical analysis was performed the results indicated that there were significant decreases in body weight, percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
20

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 26 publications
1
26
0
20
Order By: Relevance
“…In group M, the significantly higher values of bM, FFM, and SMM, lower levels of bF, with relatively minor differences in bH were undoubtedly the result of more advanced development, longer training experience, and larger training loads. As mentioned, various anthropometric measures were found to be highly correlated with TKD performance [4,9,10]. This was confirmed by our study, where the very high correlations observed between bM, FFM, SMM, and P max are indicative of a series of cause-effect relationships.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…In group M, the significantly higher values of bM, FFM, and SMM, lower levels of bF, with relatively minor differences in bH were undoubtedly the result of more advanced development, longer training experience, and larger training loads. As mentioned, various anthropometric measures were found to be highly correlated with TKD performance [4,9,10]. This was confirmed by our study, where the very high correlations observed between bM, FFM, SMM, and P max are indicative of a series of cause-effect relationships.…”
Section: Discussionsupporting
confidence: 87%
“…In a study by Noh et al [8], the -80 kg weight class had the highest mesomorphic and the lowest endomorphic component value. Other works have indicated that even 8 weeks of pre-season TKD training is beneficial in reducing bM, %bF, and fat tissue [9], thus impacting technical skills and moves. The beneficial effects of TKD training were also indicated by Toskovic et al [13], who estimated that around 30 min of TKD practice three times per week was sufficient in controlling bM and enhancing fat loss.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most effective criterion in determining performance in sports is body height and body weight. Body height and body weight are among the anthropometrical prerequisites which are needed in the selection athletes and their development (Sevim, 2002;Savaş & Uğraş 2004). Therefore, it is highly important to deal with body composition and the skill of jumping which are very important in especially volleyball together.…”
Section: Introductionmentioning
confidence: 99%